provisions With examples of its jurisprudential Negating thedifference and its effect on inferring the legal applications (Journal of Human Sciences, 2020)
Negating the difference and its effect on inferring the legal provision This research deals with (denying the difference and its effect on inferring the legal rulings with examples of its jurisprudential applications) and has divided it into three sections, which dealt in the first topic: the definition of the denial of the difference in terms, methods and its truth among the fundamentalists, which in turn is three demands, the first requirement: the definition of the negation of the difference in language and idiomatically The second requirement: absolute expressions on the negation of the difference, the third requirement: methods of eliminating the negation of the difference between the origin and the branch. According to the fundamentalists, as for the third topic, it dealt with the types of denial of the difference with examples of its jurisprudential applications, and it contains three demands, the first requirement: the types of negation of the difference and the second requirement: jurisprudential models in which the difference was excluded, while the third requirement was: jurisprudential models denying the difference in which an assumption is often contested. For certainty.